The effects of diets formulated on an ideal protein basis on growth performance and carcass characteristics of finishing gilts housed in a hot diurnal environment - J Lopez; G W Jesse; D Spiers; B A Becker; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1992)
Forty-eight finishing gilts (initial weight = 155 ± 2 lb) were randomly assigned to one of eight experimental treatments in a 2 x 2 x 2 factorial arrangement with main effects including dietary lysine (.60 vs 1.00%), source of amino acid fortification (intact protein vs synthetic amino acids formulated on an ideal protein basis) and environmental temperature (thermoneutral (TN): 68Â°F vs hot, diurnal (HS): 82 to 95 Â°F). The ideal protein diets were formulated by using corn and soybean meal to meet the 5th limiting amino acid with additions of synthetic lysine, threonine, tryptophan, methionine, or isoleucine to meet the pigs estimated requirement. The ratios of other total amino acids relative to lysine were: threonine 66%, tryptophan 17%, methionine and cystine 56%, and isoleucine 63%. Average daily gain (ADG), average daily feed intake (ADFn, and feed efficiency (FIG) were similar for gilts fed the intact and ideal proteins diets. Increasing dietary lysine improved d 0-14 ADG and resulted in a numerical improvement for the overall study. Gilts in the HS environment ate less feed and had lower ADG than gilts at TN. A temperature X lysine interaction was observed for FIG. Increasing dietary lysine had no effect on FIG of gilts in the TN environment, but improved FIG of gilts in the HS environment. Carcass protein and lipid contents were improved for gilts in the HS environment and by increased dietary lysine. Accretion rates for protein and lipid, backfat thickness, and longissimus muscle area were improved in gilts fed 1.00% lysine. The source of amino acid fortification did not influence carcass characteristics. In conclusion, increased dietary lysine improved FIG and carcass leanness in gilts to a greater extent in HS than TN environments. However, no improvements were observed in growth performance or carcass traits from feeding ideal protein diets.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Pigs; Lysine; Growth; Heat stress